2011
DOI: 10.1007/s11240-011-9945-3
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of anthocyanin-producing cell suspension cultures of Cleome rosea Vahl ex DC. (Capparaceae)

Abstract: The effects of different levels of Murashige and Skoog (MS) basal medium, 2,4-dichlorophenoxyacetic acid (2,4-D), and sucrose on anthocyanin production and biomass accumulation of cell suspension cultures of Cleome rosea were investigated. Cultures were established in liquid MS medium containing 30 g l -1 sucrose and supplemented with 0.90 lM 2,4-D. Proliferating cell suspension cultures achieved the highest growth capacity, a fourfold increase in biomass accumulation, following subculture at the exponential g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 40 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…In addition, it was observed that the root cultures in 7 and 10% w/v sucrose concentration media became tangled and turned brown after 4 weeks of inoculation. This result indicates that the roots were repressed when sucrose level was increased and this could be due to high osmotic pressure of the medium as noted in the study of P. ginseng (Kim et al 2005) and Hypericum perforatum (Cui et al 2010) adventitious root cultures, and cell suspension cultures of C. rosea (Simões-Gurgel et al 2011). Although the root FW decreased in higher sucrose concentration level, the root DW depicted dissimilar pattern which show insignificant difference between 2 and 10% w/v sucrose concentrations (P \ 0.05).…”
Section: Sucrose Concentrationsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, it was observed that the root cultures in 7 and 10% w/v sucrose concentration media became tangled and turned brown after 4 weeks of inoculation. This result indicates that the roots were repressed when sucrose level was increased and this could be due to high osmotic pressure of the medium as noted in the study of P. ginseng (Kim et al 2005) and Hypericum perforatum (Cui et al 2010) adventitious root cultures, and cell suspension cultures of C. rosea (Simões-Gurgel et al 2011). Although the root FW decreased in higher sucrose concentration level, the root DW depicted dissimilar pattern which show insignificant difference between 2 and 10% w/v sucrose concentrations (P \ 0.05).…”
Section: Sucrose Concentrationsupporting
confidence: 54%
“…For example, when the MS medium strength was reduced from 1 to 1/4, rooting percentages of Syzygium alternifolium were increased and the 1/2MS medium was found more satisfactory for the root growth (Sha Valli Khan et al 1999). Simões-Gurgel et al (2011) found that the use of 1/2MS medium resulted in higher anthocyanin production in cell suspension culture of Cleome rosea when compared to cultures grown on 1MS or 1/4MS medium. In another study, medium replenishment strategy was implemented to increase biomass and metabolite production, e.g.…”
Section: Ms Medium Strengthmentioning
confidence: 91%
“…The accumulation of colours and pigments in cell culture can be facilitated by the direct selection of high-producing cell lines (Sada and Shuler 1989). For anthocyanin production, the new sources such as from Cleome rosea (Simoes-Gurgel et al 2011), Rosa hybrida L. (Ram et al 2011), Crataegus sinaica (Maharik et al 2009) and Melastoma malabathricum (See 2008), cell cultures have been established in recent years. Several methods have been used to improve the production of secondary metabolites in plant cell culture systems, i.e., elicitation (Knorr et al 1994), two phase culture (Brodelius and Pedersen 1993), hairy root culture (Choi et al 1995), immobilization (Toivnen 1993) and DNA methylation (Baranek et al 2010;Kiselev et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of sucrose (29-88 mM) to culture media under both ambient and elevated CO 2 conditions led to a reduction in shoot and root performance of in vitro plantlets (Suriyan et al 2011). Increasing levels of sucrose above 30 g/L in the cell suspension cultures of Cleome rosea resulted in a drastic reduction in biomass accumulation (Claudia et al 2011). However, most of the studies focused on the initial sucrose concentration during culture rather than on sugar contents at different growth stages.…”
Section: Introductionmentioning
confidence: 99%